Role of fibroblast growth factor 2 and Wnt signaling in anabolic effects of parathyroid hormone on bone formation - Fei, Yurong (2012)
Osteoporosis poses enormous health and economic burden worldwide. One of the very few anabolic agents for osteoporosis is parathyroid hormone (PTH). Although great progress has been made since the FDA approved PTH in 2002, the detailed mechanisms of the bone anabolic effects of intermittent PTH treatment is still not well understood. PTH bone anabolic effect is regulated by extracellular factors. Maximal bone anabolic effect of PTH requires fibroblast growth factor 2 (FGF2) signaling, which might be mediated by transcription factor activating transcription factor 4 (ATF4). Maximal bone anabolic effect of PTH also requires Wnt signaling. Particularly, Wnt antagonists such as sclerostin, dickkopf 1 (DKK1) and secreted frizzled related protein 1 (sFRP1) are promising targets to increase bone formation. Interestingly, FGF2 signaling modulates Wnt/β-Catenin signaling pathway in bone. Therefore, multiple signaling pathways utilized by PTH are cross talking and working together to promote bone formation. Extensive studies on the mechanisms of action of PTH will help to identify new pathways that regulate bone formation, to improve available agents to stimulate bone formation, and to identify potential new anabolic agents for osteoporosis.